2006
DOI: 10.1074/jbc.m605549200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Missing Links in Prokaryotic Pentose Oxidation Pathways

Abstract: The pentose metabolism of Archaea is largely unknown. Here, we have employed an integrated genomics approach including DNA microarray and proteomics analyses to elucidate the catabolic pathway for D-arabinose in Sulfolobus solfataricus. During growth on this sugar, a small set of genes appeared to be differentially expressed compared with growth on D-glucose. These genes were heterologously overexpressed in Escherichia coli, and the recombinant proteins were purified and biochemically studied. This showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
189
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(194 citation statements)
references
References 77 publications
4
189
0
1
Order By: Relevance
“…However, the data do not give a good fit to the classical substrate inhibition equation, indicating that other factors may influence the dependence of enzyme velocity on substrate concentration. Interestingly, the purified D-arabinonate dehydratase identified in S. solfataricus is also subject to what appears to be substrate inhibition (8).…”
Section: A Proposed Catabolic Pathway For D-xylose and L-arabinose-mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the data do not give a good fit to the classical substrate inhibition equation, indicating that other factors may influence the dependence of enzyme velocity on substrate concentration. Interestingly, the purified D-arabinonate dehydratase identified in S. solfataricus is also subject to what appears to be substrate inhibition (8).…”
Section: A Proposed Catabolic Pathway For D-xylose and L-arabinose-mentioning
confidence: 99%
“…Brouns et al (8) reported that S. solfataricus gene SSO3117 encodes an aldehyde dehydrogenase that, when recombinantly expressed, possessed catalytic activity with 2,5-dioxopentanoate, glyceraldehyde, and glycolaldehyde. We have confirmed this observation, found that the enzyme is specific for NADP ϩ , and report the kinetic parameters for the substrates pentanedial (as an analog of 2,5-dioxopentanoate) and glycolaldehyde (Table 1).…”
Section: A Proposed Catabolic Pathway For D-xylose and L-arabinose-mentioning
confidence: 99%
See 2 more Smart Citations
“…␣-KGSA dehydrogenase enzymes involved in the catabolism of L-arabinose, D-glucarate, D-galactarate, and hydroxy-L-proline have also been characterized (25,52,53). To investigate whether the reducedgrowth phenotype of the hypH mutant on trans-4-L-Hyp may be due to the presence of other ␣-KGSADH-like enzymes, we searched the S. meliloti genome for other annotated dehydrogenases and identified the most similar as AraE, which functions as an ␣-KGSADH in the catabolism of L-arabinose (18).…”
Section: Discussionmentioning
confidence: 99%